PENGARUH STORE ATMOSPHERE DAN HARGA TERHADAP LOYALITAS PELANGGAN - Labiba, Ahmad Izza; Moko, Wahdiyat (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Today's people have a great interest in visiting cafes which provide many facilities for hanging out and can be said to be one of the favorite choices favored by all groups, from the young to the old. Each cafe has a different strategy in order to captivate its customers. Loyal customers will provide profitability because loyal customers can show positive attitudes and behavior and can provide positive recommendations so that they can become promotional tools. This study aims to determine the effect of store atmosphere and price on customer loyalty. This type of research is explanatory research which explains the causal relationship between variables through hypothesis testing. This study used a sample of 100 respondents using accidental sampling technique. Methods of data collection using a questionnaire. The data analysis technique used descriptive analysis, multiple linear regression analysis and t test. Data analysis using SPSS (Statistical Product and Services Solution) version 21 to facilitate research. The results of the analysis show that the store atmosphere variable has a negative effect on customer loyalty and the price variable has a significant negative effect on customer loyalty.